Constitutional LZTR1 mutation presenting with a unilateral vestibular schwannoma in a teenager. Issue 5 (19th April 2017) - Gripp, K.W.; Baker, L.; Kandula, V.; Piatt, J.; Walter, A.; Chen, Z.; Messiaen, L.
Abstract : Schwannomatosis is a rare neurofibromatosis clinically diagnosed by age‐dependent criteria, with bilateral vestibular schwannoma and/or a constitutional NF2 mutation representing exclusion criteria. Following SMARCB1 germline mutations, constitutional mutations in LZTR1 were discovered. We report on the molecular investigation in a patient presenting at 14 years with a unilateral vestibular schwannoma, ultimately causing blindness and unilateral hearing loss, in the absence of other schwannomas or a positive family history. In DNA derived from frozen tumor tissue, a comprehensive NF2, SMARCB1 and LZTR1 analysis showed an NF2 truncating mutation c.1006_1021delins16; an LZTR1 mutation c.791+1G>A; and a partial 22q deletion including NF2, SMARCB1 and LZTR1 . Sequence analysis on peripheral blood derived DNA showed the LZTR1 mutation to be constitutional, but the NF2 mutation and partial 22q deletion were not found, indicating them to be somatic events. RNA‐based targeted analysis confirmed missplicing of LZTR1 intron 8, predicted to result in a premature stop codon. This LZTR1 mutation was paternally inherited. While isolated vestibular schwannoma or NF2 may be considered in a young individual with a unilateral vestibular schwannoma, this report suggests that LZTR1 ‐related schwannomatosis be added to this differential diagnosis. Abstract :